Organizational Development Approach, Implementation of Integrated Reporting Course (A Role Elevating for International Accounting Curriculum) - Syaiful Hifni; Akhmad Sayudi; Atma Hayat (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine the organizational development approach in the internationalization of the accounting curriculum by designing a new course for integrated reporting <IR>. Design/methodology/approach - This study measures the strategic, social, technical and administrative aspects of the relevant course materials, and learning outcomes objectives in the design of the new <IR> course. The target population is an accounting higher education implementing entity in Kalimantan. The sample of this research entity is 150 (one hundred and fifty) respondents. Consists of 75 (seventy five) lecturers, and 75 (seventy five) students (strata 1, strata 2) in higher education accounting (public and private) in South Kalimantan Province, Indonesia. Findings: at the strategic level with fundamental concepts, at the social level with social sustainability reporting, and at the administrative policy implementation there is an influence on the implementation of the new <IR> courses. Meanwhile, at the strategic level with guidelines, the technical level with the main requirements and the technical level with content elements, it shows that these variables have no effect on the implementation of the new <IR> course. Practical Implications: Development of <IR> course design related to synergy with the complete list of courses in the accounting higher education curriculum. <IR> course design provides graduate competencies from academic, professional and social perspectives. Originality/Value - This study makes a relevant contribution, as it presents a normative model for the <IR> course syllabus design initiative in higher education accounting in an international context.